Synthesis and characterization of KCC-1 prepared from waste material for heavy metal removal - Setiabudi, Herma Dina (2019)
Lead (Pb(II)) is one of the most toxic metals found in water bodies through industrial activities which can cause severe hazardous impacts to living organisms even at trace levels. Therefore, several methods for lead removal have been investigated, including the adsorption process. Regarding the selection of adsorbent, fibrous silica nanosphere (KCC-1) has attracted considerable attention owing to its high surface area and fibrous silica morphology. However, owing to the high cost of the commercial silica precursor, utilization of rice husk ash (RHA) (SiO2 = 95.44%) as alternative silica source seems to be a promising approach and the application of amine functionalization will enhance its adsorption capacity. Thus, the main objective of this study is to synthesize and characterize KCC-1(RHA) for Pb(II) removal. The characterization analyses showed that the synthesized KCC-1(RHA) consists of fibrous silica morphology with high surface area (SBET, KCC-1(RHA) = 220 m2/g, SBET, NH₂/KCC-1(RHA) = 274 m2/g) comparable with KCC-1 synthesized from commercial silica source, indicating the successful formation of KCC-1 structure from RHA. The influences of prominent parameters (initial concentration (X1), adsorbent dosage (X2) and time (X3)) on Pb(II) removal was evaluated by RSM, and the optimal conditions were achieved at X1 = 322.06 mg/L, X2 = 2.4 g/L and X3 = 117 min, with 74.50% of Pb(II) removal from aqueous solution. The experimental data were analyzed using Langmuir, Freundlich, Temkin, and Dubinin-Redushkevich isotherm models, and were found to follow Langmuir isotherm model with maximum adsorption capacity of 26.954 mg/g and high correlation coefficient (R2 = 0.9934), implying monolayer adsorption occurred on the homogenous surface of the adsorbent. Pseudo-first order, Pseudo-second order, and Elovich kinetic models were tested with the experimental data, and Pseudo-second order kinetic model was best fitted the adsorption process, indicating that the adsorption process most likely controlled by the chemisorption process and the rate of reaction is directly proportional to the number of active sites on the surface of adsorbent. The regeneration and reusability studies revealed that KCC-1(RHA) performs good adsorption-desorption for five cycles with a moderate reduction in the percentage of Pb(II) removal. This study revealed that RHA demonstrated great potential as silica precursor of KCC-1 for excellent Pb(II) adsorption from aqueous solution.